Alzheimer's Disease Clinical and Research Update for Health Care Practitioners. (4th September 2013) - DeFina, Philip A.; Moser, Rosemarie Scolaro; Glenn, Megan; Lichtenstein, Jonathan D.; Fellus, Jonathan
Abstract : Of the approximately 6.8 million Americans who have been diagnosed with dementia, over 5 million have been diagnosed with Alzheimer's Disease (AD). Due to the rise in the aging population, these figures are expected to double by 2050. The following paper provides an up-to-date review of clinical issues and relevant research. Research related to the methods of the earliest possible detection of AD is ongoing. Health care professionals should play a critical role in differentially diagnosing AD patients, as well as supporting their families. Novel interventions, including medications, natural supplements, and behavioral techniques, are constantly appearing in the literature. It is necessary for the health practitioner to remain current, regarding AD, as such information will facilitate better care for patients and their families.